Patient record management system (PRMS) - Mohamad Zahir, Abdul Talib (2011)
This Patient Record Management System is a renewal of the existing system in the Student Health Unit at the University Malaysia Pahang.This system involves the user of the staff at the health unit itself,which handles the registration of patients at the health unit.The purpose of this reform is that the patient record management system available to the health unit is no longer efficient use in the present day. The effect of these inefficient causing frequent errors when employee entering information to their patients that can affect the performance and quality of services at the student health unit.This patient record management system has three main modules,namely a new patient record, see the status of the number of patients who come to the unit each day and the type of disease that often encountered by students in the TJItvIP and make a communication medium between patient and doctor. The development of this system has given an alternative to the Student Health Unit UMP to use computerized systems to manage their services.